2003
DOI: 10.1523/jneurosci.23-22-08051.2003
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Receptor Knock-In Mice and Hyperekplexia-Like Phenotypes: Comparisons with the Null Mutant

Abstract: Strychnine-sensitive glycine receptors (GlyRs) inhibit neurotransmission in the spinal cord and brainstem. To better define the function of this receptor in vivo, we constructed a point mutation that impairs receptor function in the alpha1-subunit and compared these knock-in mice to oscillator (spdot) mice lacking functional GlyR alpha1-subunits. Mutation of the serine residue at amino acid 267 to glutamine (alpha1S267Q) results in a GlyR with normal glycine potency but decreased maximal currents, as shown by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 50 publications
4
59
2
Order By: Relevance
“…First, currents elicited from oocytes upon application of a maximal concentration of glycine (10 mM) were determined. The magnitudes of these responses provide a measure of the expression level and function of receptors (17). There was a small but significant difference (Ͻ30%) between the maximal currents elicited by homomeric wt and S267C receptors (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, currents elicited from oocytes upon application of a maximal concentration of glycine (10 mM) were determined. The magnitudes of these responses provide a measure of the expression level and function of receptors (17). There was a small but significant difference (Ͻ30%) between the maximal currents elicited by homomeric wt and S267C receptors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Culture and transfection of human embryonic kidney 293 cells and single-channel recordings from outside-out patches were conducted as described previously (17). Outside-out macropatch recordings were similar to single-channel recordings except that the patch electrodes had lower resistances (3-6 M⍀) to promote the formation of larger patches.…”
Section: Methodsmentioning
confidence: 99%
“…In a1S267N receptors, we observed an increased EC 50 for glycine and no change in I max , while a1S267Q channels exhibit a normal EC 50 and reduced I max. 17 The phenotypic presentation in both cases, however, is compatible with dominant hyperekplexia. While ethanol potentiation was virtually absent in HEK293 expressed homomeric a1(S267N) receptors, some ethanol sensitivity is retained in Xenopus oocyte expression, as potentiation depends on the expression system.…”
mentioning
confidence: 87%
“…While ethanol potentiation was virtually absent in HEK293 expressed homomeric a1(S267N) receptors, some ethanol sensitivity is retained in Xenopus oocyte expression, as potentiation depends on the expression system. 14,17 This study shows that a disease-related receptor allele harbours the potential to modify drug responses in affected patients by reducing GlyR affinity and efficacy. Given the low phenotypic penetrance of the disease allele GLRA1(S267N) in one of our patients, however, this allelic polymorphism may not be clinically apparent.…”
mentioning
confidence: 91%
“…Some studies have reported that mutations can dramatically alter the functional properties of 1GlyR [9]. The discovery that 1GlyR directly interacts with Gβγ has provided secondary supporting evidence for these findings [10,11].…”
Section: Introductionmentioning
confidence: 98%